Integrated Control of Eimeria spp. in Broiler Chickens with Floor Brooding Technology in Industrial Production - E. O. Kachanova; R. T. Safiullin (Российский паразитологический журнал, 2019)
The purpose of the research is to test the effectiveness of the integrated control of exogenous and endogenous stages of Eimeria spp. in poultry farms with floor brooding broiler chickens.Materials and methods. The study was conducted in 10 poultry houses of the Nezhegolskaya poultry farm of the Belaya Ptitsa agricultural holding of the Belgorod Region during one production cycle in May–June of 2017. A 4% solution of delegol Pro was used as a disinfectant at a flow rate of 0.5 l per m² at an exposure of 2 hours. As a method of preparations against endogenous stages, the chickens were administered the ionophore feed antibiotic salinomycin 12% at the recommended dose with food, and toltrazuril 2.5% (baykoks), which was given to the chickens of 8–10 days age with drinking water in the recommended dose for 72 hours at the rate of 1 liter of the drug per 1000 liters of water. The initial contamination of the houses by Eimeria oocysts, the effectiveness of the delegol Pro and the combined use of salinomycin and toltrazuril were established for chickens according to the results of studies of bedding samples before and after the administration of toltrazuril, as well as before slaughter of an experimental batch of chickens. The effectiveness of the integrated control of exogenous and endogenous stages of Eimeria spp. was established, and the species composition of Eimeria spp. was identified.Parasitological studies of the bedding and scrapings were done in the laboratory of the All-Russian Scientific Research Institute of Fundamental and Applied Parasitology of Animals and Plants named after K. I. Skryabin by the combined method of Darling. The prevalence (PI) and intensity (II) of the eimeriotic infection in the bedding and scrapings were established by counting the number of oocysts in 1 g of scrapings using the McMaster egg counting chamber. The species composition of Eimeria spp. was determined after the collection and cultivation of oocysts. Morphometry of eimeria oocysts was carried out. The effectiveness of the comprehensive control of the exogenous and endogenous stages of coccidia in a poultry farm with a floor brooding of broiler chickens was determined as the efficiency or percentage reduction in the number of oocysts in bedding samples after slaughter of the previous and experimental batch of chickens, which was calculated by the formula.Results and discussion. In scrapings from the floor of 10 houses, before disinfection, a high contamination of the floor of the houses by eimeria oocysts (Eimeria spp.) was found. The average extent of eimeriotic infection was 53.33%, and the intensity was 12.23±5.15 thousand oocysts/g of scrapings. In scrapings from the floor 24 hours after the treatment of the houses with delegol Pro, eimeria oocysts were found in all 10 houses, but a decrease in PI to 49.99% and II to 7.6±2.46 thousand oocysts/g scrapings was noted. During the disinfestation of the oocysts, the Eimeria spp. was not completely destroyed, which confirms the inadequacy of the control of only the exogenous stages of coccidia. Therefore, the second stage of the comprehensive program was the control of endogenous stages of Eimeria spp. Strong bedding pollution was found after slaughter of the previous batch of chickens. The average PI for 10 houses in the bedding was 51.66%, with an average II of 11.96±5.97 thousand oocysts/g. When examining the bedding of an experimental batch of chickens before giving toltrazuril, the average PI was 25%, II was 6.67±6.21 thousand oocysts/g bedding. The average PI in the bedding one week after administration of 2.5 % toltrazuril was 8.35% with an II of 1.65±1.84 thousand oocysts/g; two weeks after administration of the drug PI was 51.66% with II 11.62±14.46 thousand oocysts/g; after three weeks, PI was 76.66%, II was 8.88±5,82 thousand oocysts/g; after four weeks, PI was 81.66%, II was 7.48±2.55 thousand oocysts/g. Before slaughtering an experimental batch of broilers eimeria oocysts were found in samples of the bedding in 9 houses. It should be noted that the average PI for 10 houses in the bedding was 34.99% with II of 3.56±1.34 thousand oocysts/g, which is significantly lower than the same indicators after slaughter of the previous batch of chickens, where PI was 51.66%, and II was 11.96±5.97 thousand oocysts/g. The species composition of eimeria oocysts from bedding samples was determined at 2 and 4 weeks after the 2.5% toltrazuril was administered with Eimeria acervulina (20%), E. brunetti (33.3%), E. maxima (33.3%), E. tenella (13.4%). The results of a study of the effectiveness of the integrated control of exogenous and endogenous stages of coccidia in an industrial poultry farm with a floor brooding of broiler chickens showed a 70.2 % intensity of this program.